PENGEMBANGAN WISATA BERBASIS ESD (EDUCATION FOR SUSTAINABLE DEVELOPMENT) DI DESA MANGLI - Galih Istiningsih; Dwitya Sobat Adi Dharma; Sri Hartatik (Jurnal Bakti Masyarakat Indonesia, 2022)
The purpose of this service is to develop tourism potential by activating tourism awareness groups by managing waste into hydroponics and eco prints that increase sustainable economic resilience in the Mangli Tourism Village. The problem faced is that waste is increasingly piling up around the location and does not yet have a tourism development organizational structure and the limitations of residents in managing tourism. In addition, there are target problems: 1) The number of residents of Dusun Mangli, the majority of whom do not work as much as 15.9%, 2) 75% of visitors do not throw garbage in its place, and 3) the Lack of waste management. The target number is around 15 members of the Mangli Pokdarwis. Community Service is carried out in three stages, namely: a) socialization of the concept of ESD, b) the practice of assisting waste processing with eco print and hydroponics into business opportunities, c) formation of pokdarwis, and evaluation of tourism development. Assistance to tourism administrators provides education and social and economic benefits. The results of the service are taking care of licensing for pioneering tourism work programs, counseling from and teams, catfish hydroponic training, eco print batik training, focus group discussions, and the establishment of program sustainability through ecoliteracy pokdarwis in Mangli. The service outputs are 1) the concept of ESD in Mangli Tourism, 2) waste products and their marketing, and 3) the community/organizational structure of Pokdarwis for program sustainability. The conclusion of this service is the creation of the ESD-Based Mangli Village Pilot program in the form of Catfish Hydroponics and Batik Ecoprint, namely through the learning-by-doing method to improve the economy and develop community creativity in processing plastic waste and leaves and flowers in Mangli Hamlet, Kaliangkrik. ABSTRAK: Tujuan  pengabdian ini untuk pengembangan potensi wisata dengan mengaktifkan  kelompok sadar wisata dengan mengelola sampah menjadi hidroponik dan ecoprint yang meningkatkan ketahanan ekonomi berkelanjutan di Desa Wisata Mangli. Permasalahan yang dihadapi adalah sampah yang semakin menumpuk di sekitar lokasi dan belum memiliki struktur organisasi pengembangan wisata serta keterbatasan warga dalam mengelola wisata. Selain itu terdapat permasalahan sasaran 1) Jumlah warga Dusun Mangli yang mayoritas tidak bekerja sebanyak 15,9% , 2) 75% pengunjung tidak membuang sampah pada tempatnya, dan 3) Kurangnya dalam pengelolaan sampah tersebut.jumlah sasaran sekitar 15 anggota pokdarwis Mangli. Pegabdian dilaksanakan dengan tiga tahap yaitiu: a) sosialisasi konsep ESD, b)  praktik pendampingan  pengolahan sampah dengan ecoprint dan hidroponik menjadi peluang usaha, c) pembentukan pokdarwis dan evaluasi pengembangan wisata. Pendampingan  kepada pengurus wisata memberikan da,pak Pendidikan, sosial dan ekonomi.  Hasil pengabdian adalah mengurus perijinan program kerja perintisan  wisata, penyuluhan dari  dan tim, pelatihan hidroponik lele, pelatihan batik  ecoprint, focus grup discussion, terbentuknya keberlanjutan program melalui pokdarwis tali ekoliterasi di mangli. Luaran pengabdian berupa: 1) konsep ESD di Wisata Mangli, 2) produk limbah sampah dan pemasarannya, 3) komunitas/ struktur organisasi pokdarwis untuk keberlanjutan program. Kesimpulan dalam pengabdian ini adalah terciptanya program Rintisan Kampung Mangli Berbasis ESD yang berbentuk Hidroponik Lele dan Batik Ecoprint yaitu melalui metode learning by doing dengan tujuan meningkatkan perekonomian dan mengembangkan kreativitas masyarakat dalam mengolah limbah plastik dan dedaunan serta bunga-bunga di Dusun Mangli, Kaliangkrik.